Do Marmorkrebs, Procambarus fallax f. virginalis, threaten freshwater Japanese ecosystems? - Faulkes, Zen (2012)
Background: One marbled crayfish, Marmorkrebs, Procambarus fallax f. virginalis (Hagen, 1870), was discovered in a natural ecosystem in Japan in 2006. Because Marmorkrebs are parthenogenetic, they could establish a population from only a single individual, and thus pose a risk for becoming established in Japan, as they have in other countries. There are two major reasons to be concerned about the possibility of Marmorkrebs establishing viable populations in Japan. First, Japan's only endemic crayfish, Cambaroides japonicus (De Haan, 1841), lives throughout Hokkaido and is endangered. Introduced Marmorkrebs are potential competitors that could further threaten C. japonicus. Second, Marmorkrebs live in rice paddies in Madagascar and consume rice. Marmorkrebs populations could reduce rice yields in Japan.Results: We created five models in MaxEnt of the potential distribution of Marmorkrebs in Japan. All models showed eastern Honshu, Shikoku and Kyushu contain suitable habitats for Marmorkrebs. Hokkaido, the main habitat for C. japonicus, contained much less suitable habitat in most models, but is where the only Marmorkrebs in Japan to date was found.Conclusions: Marmorkrebs appear to be capable of establishing populations in Japan if introduced. They appear to pose minimal threat to C. japonicus, but may negatively affect rice production. © 2012 Faulkes et al.; licensee BioMed Central Ltd.